Intelligent optical networking for multilayer survivability. - De Maesschalck, S. (IEEE Communications magazine)
In recent years, telecommunication networks have faced explosive (IP) traffic growth. As traffic keeps growing, network reliability gains more and more importance. This article investigates to which extent switched connections and fast connection provisioning, typical for intelligent optical networks (IONs), can be used to provide resilience in an IP-over-optical multilayer network scenario. This solution, based on transport network flexibility, is compared with more traditional static multilayer resilience schemes in terms of cost (capacity) requirements and operational (dis)advantages